2018
DOI: 10.1093/ajcn/nqy108
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of dietary nitrate intake in humans: a systematic review

Abstract: Background The nitrate content of foods and water is highly variable, which has implications for the compilation of food-composition databases and assessment of dietary nitrate intake. Objective A systematic review was conducted to ascertain the dietary assessment methods used and to provide estimates of daily nitrate intake in humans. Design Relevant article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 81 publications
5
56
1
Order By: Relevance
“…Questions where current evidence is ambiguous or where there is no correct response (ie, the answer reflects a belief or opinion on inorganic nitrate) were not included in the Index. Recently published systematic reviews and meta-analyses were used to inform these decisions 17 24 30 31…”
Section: Methodsmentioning
confidence: 99%
“…Questions where current evidence is ambiguous or where there is no correct response (ie, the answer reflects a belief or opinion on inorganic nitrate) were not included in the Index. Recently published systematic reviews and meta-analyses were used to inform these decisions 17 24 30 31…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that supplemental NO 3 − is ineffective at eliciting meaningful physiological changes in individuals habitually consuming a high NO 3 − diet. Nevertheless, as population intake of NO 3 − is typically low — Babateen et al [ 93 ] reported a median intake of 108 mg/d in healthy individuals. With very few individuals regularly consuming NO 3 − levels to match those provided through supplementation [ 160 ], high habitual NO 3 − intake is unlikely to explain a lack of response to NO 3 − supplementation in most ‘non-responders’.…”
Section: Main Textmentioning
confidence: 99%
“…Indeed, an investigation conducted on behalf of the WHO in 2004 found no exposure-response relationship between dietary NO 3 − and methemoglobinemia in infants [ 193 ]. It is also worth noting that although some studies report mild adverse symptoms with high NO 3 − intake such as nausea and sickness, to the authors knowledge, no serious adverse events have ever been reported in clinical trials administering NO 3 − [ 1 , 93 ].…”
Section: Main Textmentioning
confidence: 99%
“…It is known that the antioxidant capacity changes under exposure to various xenobiotics, as well as those derived from foods [21]. The general toxic effects of ACR and SN (V) and (III), and nutritional questionnaires on the intake of these substances in the diet are relatively numerous and well-known [20,22,23,24], but there is still a lack of data evaluating the impact of these compounds on the total cellular pool of free thiols in blood plasma. The aim of this study was to estimate the influence of ACR and SN (V) and (III), derived from the diet, on the total pool of free thiols in blood plasma in young healthy people.…”
Section: Introductionmentioning
confidence: 99%